The 20-million-year old lair of an ambush-predatory worm preserved in northeast Taiwan - Yu-Yen Pan (Nature Portfolio, 2021)
Abstract The feeding behavior of the giant ambush-predator “Bobbit worm” (Eunice aphroditois) is spectacular. They hide in their burrows until they explode upwards grabbing unsuspecting prey with a snap of their powerful jaws. The still living prey are then pulled into the sediment for consumption. Although predatory polychaetes have existed since the early Paleozoic, their bodies comprise mainly soft tissue, resulting in a very incomplete fossil record, and virtually nothing is known about their burrows and behavior beneath the seafloor. Here we use morphological, sedimentological, and geochemical data from Miocene strata in northeast Taiwan to erect a new ichnogenus, Pennichnus. This trace fossil consists of an up to 2 m long, 2–3 cm in diameter, L-shaped burrow with distinct feather-like structures around the upper shaft. A comparison of Pennichnus to biological analogs strongly suggests that this new ichnogenus is associated with ambush-predatory worms that lived about 20 million years ago.